2022
DOI: 10.1021/acsanm.2c01189
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Alloy Nanostructures for Optical Sensing of Hydrogen

Abstract: Pd nanoalloys show great potential as hysteresis-free, reliable hydrogen sensors. Here, a multiscale modeling approach is employed to determine optimal conditions for optical hydrogen sensing using the Pd−Au−H system. Changes in hydrogen pressure translate to changes in hydrogen content and eventually the optical spectrum. At the single particle level, the shift of the plasmon peak position with hydrogen concentration (i.e., the "optical" sensitivity) is approximately constant at 180 nm/c H for nanodisk diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This enabled the measurement of optical pressure composition isotherms (Figure 2c). Later studies 33,34,47 and first-principles calculations 56,57 revealed direct proportionality between the H concentration in Pd and Δλ peak .…”
Section: Plasmonic Hydrogen Sensingmentioning
confidence: 99%
“…This enabled the measurement of optical pressure composition isotherms (Figure 2c). Later studies 33,34,47 and first-principles calculations 56,57 revealed direct proportionality between the H concentration in Pd and Δλ peak .…”
Section: Plasmonic Hydrogen Sensingmentioning
confidence: 99%
“…Moreover, the increase in the number of holes is greatest between 0 and 50%, echoing the composition dependence observed for the spectra. As discussed in more detail in refs and , one can understand this trend with composition as being the result of the gradual filling/depletion of the d-band when starting from the pure group-10/group-11 element. This analysis thus demonstrates that the trends observed here are not strongly affected by NP size or shape and largely represent the behavior of the surface (as opposed to the full NP).…”
Section: Resultsmentioning
confidence: 99%
“…As our model system we use the AuPd alloy system, which we have widely used and characterized in the context of plasmonic hydrogen sensors. ,,,, Such sensors are based on the principle that hydrogen absorption into interstitial sites of metallic hosts, such as Pd and its alloys but also other systems like Ni, Mg, Y, Hf, , and Ta, and their alloys with Pd, induces distinct changes in their electronic structure, and thus optical response in general and LSPR in particular. Importantly, these changes are proportional to the hydrogen concentration/partial pressure in their surroundings. From the application perspective, such sensors are attractive since their optical signal transducing mechanism generates no sparks and since the entire sensor, in principle, can be miniaturized down to a single nanoparticle. , The former aspect is especially important since hydrogen–oxygen mixtures are highly flammable above the 4% H 2 lower explosive limit.…”
Section: Resultsmentioning
confidence: 99%